2014
DOI: 10.1093/ckj/sfu017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk markers associated with arterial calcification in patients with chronic kidney disease Stages 3 and 4

Abstract: BackgroundThe contribution of pro-inflammatory markers to cardiovascular (CV) risk and vascular calcification in chronic kidney disease (CKD) remains largely to be elucidated. We investigated the association between plasma levels of several biomarkers and calcification volume in three different vascular beds in CKD Stages 3 and 4 patients.MethodsThis is a cross-sectional, exploratory study in patients with an estimated glomerular filtration rate (eGFR) ≥20 and ≤45 mL/min/1.73 m2 and serum phosphorus ≥3.5 and <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
3
28
1
1
Order By: Relevance
“…This suggested that the risk factors for CAC and AVC are different, although coronary artery calcium and aortic valve calcium are, in general, positively correlated 27) . This notion might be supported by the findings in previous reports that lipoprotein(a) levels were associated with aortic valve calcification but not with coronary calcification 37) , was associated with greater coronary artery calcium volume among patients with CKD stages 3 and 4 33) . However, in several studies, including that of Kiu Weber et al, whether the observed association was independent of calcium/phosphate metabolism-related parameters was not assessed 22,33,34) .…”
Section: Logistic Regression Analysis For the Association Between -Klsupporting
confidence: 74%
See 1 more Smart Citation
“…This suggested that the risk factors for CAC and AVC are different, although coronary artery calcium and aortic valve calcium are, in general, positively correlated 27) . This notion might be supported by the findings in previous reports that lipoprotein(a) levels were associated with aortic valve calcification but not with coronary calcification 37) , was associated with greater coronary artery calcium volume among patients with CKD stages 3 and 4 33) . However, in several studies, including that of Kiu Weber et al, whether the observed association was independent of calcium/phosphate metabolism-related parameters was not assessed 22,33,34) .…”
Section: Logistic Regression Analysis For the Association Between -Klsupporting
confidence: 74%
“…This notion might be supported by the findings in previous reports that lipoprotein(a) levels were associated with aortic valve calcification but not with coronary calcification 37) , was associated with greater coronary artery calcium volume among patients with CKD stages 3 and 4 33) . However, in several studies, including that of Kiu Weber et al, whether the observed association was independent of calcium/phosphate metabolism-related parameters was not assessed 22,33,34) . Such adjustment should be performed to assess the statistical independence of the association, particularly because in the mice model of the genetic deletion of FGF23 and -Klotho, further deletion of vitamin D 1 -hydroxylase, leading to a decrease in serum 1,25(OH)2D, suppressed the ectopic arterial calcification observed 31,35) .…”
Section: Logistic Regression Analysis For the Association Between -Klsupporting
confidence: 74%
“…Wang et al (101) observed that increased circulating inflammatory proteins such as CRP and IL-6 predicted a worse prognosis with AC in CKD patients. Similarly, in a cross-sectional study, Kiu et al (45) demonstrated that elevated plasma levels of several inflammatory biomarkers such as interleukin-8 (IL-8) and interleukin-18 (IL-18) are significantly associated with AC in CKD stages 3 and 4 patients. Moreover, high TNF-␣ and interleukin-1 (IL-1) levels were shown to progress AC in patients with CKD (63).…”
Section: Mics Promotes Ac In Ckdmentioning
confidence: 96%
“…Cardiovascular disease is the leading cause of death in patients with CKD in a manner independent of risk factors, such as a history of cardiovascular disease or the presence of documented proteinuria (78,79). The increased morbidity and mortality resulting from cardiovascular disease are associated with vascular calcification in these patients.…”
Section: Phosphate and Cardiovascular Diseasementioning
confidence: 99%